Papua New Guinea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues and Statistical Appendix paper reviews the path of Papua New Guinea's external debt over the last decade. It explains the underlying macroeconomic framework to better understand the dynamics behind the external debt profile, and assesses the relative scale of the public external debt burden. It addresses the issue of public debt sustainability over the medium term. This paper also summarizes the government's ongoing reform effort aimed at reducing the size of the civil service and the payroll.